2015
DOI: 10.1002/2015jb011884
|View full text |Cite
|
Sign up to set email alerts
|

Ocean tide loading displacements in western Europe: 2. GPS‐observed anelastic dispersion in the asthenosphere

Abstract: GPS‐observed vertical ocean tide loading displacements show in Cornwall, southwest England, and in Brittany, northwest France, discrepancies of 2–3 mm with predicted values based on the isotropic Preliminary Reference Earth Model for the main tidal harmonic M2, yet in central Europe the agreement is better than 0.5 mm. By comparison of ocean tide models and validation with tide gauge observations, we demonstrate that the uncertainties in the former are too small to cause this disagreement. Furthermore, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 45 publications
3
108
0
Order By: Relevance
“…For example, using the simultaneous tropospheric approach, at CAMB a residual 12.42 h period M 2 height signal of 2.9 mm amplitude is obtained, which is explained geophysically by Bos et al . [] to arise from deficiencies in the Gutenberg‐Bullen Green's function used here, whereas it has been erroneously reduced to only 0.5 mm amplitude in the a priori fixed tropospheric solution. It can therefore be concluded that while coordinate time series noise reductions may be obtained using the a priori fixed tropospheric approach of Reuveni et al .…”
Section: Propagation Of Periodic Ground Displacement Into Gps‐estimatmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using the simultaneous tropospheric approach, at CAMB a residual 12.42 h period M 2 height signal of 2.9 mm amplitude is obtained, which is explained geophysically by Bos et al . [] to arise from deficiencies in the Gutenberg‐Bullen Green's function used here, whereas it has been erroneously reduced to only 0.5 mm amplitude in the a priori fixed tropospheric solution. It can therefore be concluded that while coordinate time series noise reductions may be obtained using the a priori fixed tropospheric approach of Reuveni et al .…”
Section: Propagation Of Periodic Ground Displacement Into Gps‐estimatmentioning
confidence: 99%
“…Crucially, however, M 2 displacement amplitudes with the optimum tuned settings remain at East 0.55 mm, North 0.55 mm, and height 2.88 mm, regardless of the amplitude of the input synthetic displacement (the maximum error, i.e., vector difference, obtained is 0.16 mm), strongly suggesting that these tuned coordinate and ZWD process noise values enable accurate 0–6 mm amplitude semidiurnal and diurnal periodic tidal ground displacements to be detected to better than 0.2 mm accuracy, and that the ~3 mm amplitude M 2 height signals in southwest England, considered by Bos et al . [] are genuine, are not caused by GPS processing error, and may be interpreted geophysically. The tests illustrated for CAMB were repeated for LERW, HERT, and ZIMM, with the same trends and same optimum process noise values found.…”
Section: Process Noise Optimizationmentioning
confidence: 99%
“…The forcing functions that generate the tides are well known from astronomical ephemerides (e.g., Meeus, 1998;Melchior, 1983). Body and load tides therefore provide valuable opportunities to investigate the interior structures of astronomical objects (e.g., Bos et al, 2015;Ito & Simons, 2011;Khan & Connolly, 2008;Lau et al, 2017;Métivier & Conrad, 2008). Body and load tides therefore provide valuable opportunities to investigate the interior structures of astronomical objects (e.g., Bos et al, 2015;Ito & Simons, 2011;Khan & Connolly, 2008;Lau et al, 2017;Métivier & Conrad, 2008).…”
Section: 1029/2018ea000462mentioning
confidence: 99%
“…Then, the elastic structure of the Earth at time scales up to a few years has also been questioned independently by tidal studies using GNSS observations. Bos et al (2015) proposed a reduction of the shear modulus of ∼10% in the asthenosphere for western Europe at the M2 tidal frequency, also suggested by Goes et al (2000) at seismic frequencies. These results are in agreement with ours, regardless of the global Earth average asthenospheric viscosity derived from our study.…”
Section: Discussionmentioning
confidence: 80%